Structural and Biological Studies of Some Bivalent Metal Macrocyclic Compounds of Biochemical Significance - Ambwani, Jitendra; L. Bansal, M.; Kaushaik, Kshama; Rani Sharma, Mamta (Asian Journal of Chemistry, 2010)
Two new macrocyclic complexes of formulae M(DCODH) (BF4)2 (where M = Cu(II) and Ni(II) and (DCODH = 2,6-pyridine dicarbonyl dichloride-oxydiacetic acid dihydrazone) have been synthesized and characterized with the help of elemental studies, IR spectral analysis and electronic spectra. These have been further screened antimicrobially for their biological studies against bacterial species, E. coli (gram negative) and S. aureus (gram positive) and fungi C. albicans, and found to possess greater biological effect as compared to the ligand fragments and the metal salts.